Response Strategies to Disruptive Innovation in Accounting: Knowledge Perspective - Ayodele, Freida Ozavize; Liu, Yao; Hasnah, Haron (2017)
Employing knowledge lens, this study empirically identifies and examines the impact of potential drivers of innovative accounting practices in a disruptive economy. The research model employed in the study was derived from the systematic integration of past empirical frameworks and findings. Data was collected using questionnaire survey which was self administered to accounting officers in a public university in Malaysia. A total of 53 usable questionnaires were collected out of 80 that were administered. The data was preliminary screened before performing the main analysis. Partial least square structural equation modelling was employed in validating the hypotheses. The findings provide evidence that accounting technologies, competent accounting staff and continuous accounting knowledge creation are potential enablers for disruptive innovative accounting practices. The research provide insight into the relevance of utilizing accounting knowledge technologies in fostering knowledge creation and innovative accounting practices. This paper is one of the first to empirically support the roles of accounting knowledge culture and accounting knowledge creation as accounting response strategy to disruptive innovations. It is recommended that this study be replicated in diverse accounting contexts to further substantiate these claims.